Anemone medicinal plants: ethnopharmacology, phytochemistry and biology - Da-Cheng Hao; Xiaojie Gu; Peigen Xiao (Elsevier, 2017)
The Ranunculaceae genus Anemone (order Ranunculales), comprising more than 150 species, mostly herbs, has long been used in folk medicine and worldwide ethnomedicine. Various medicinal compounds have been found in Anemone plants, especially triterpenoid saponins, some of which have shown anti-cancer activities. Some Anemone compounds and extracts display immunomodulatory, anti-inflammatory, antioxidant, and antimicrobial activities. More than 50 species have ethnopharmacological uses, which provide clues for modern drug discovery. Anemone compounds exert anticancer and other bioactivities via multiple pathways. However, a comprehensive review of the Anemone medicinal resources is lacking. We here summarize the ethnomedical knowledge and recent progress on the chemical and pharmacological diversity of Anemone medicinal plants, as well as the emerging molecular mechanisms and functions of these medicinal compounds. The phylogenetic relationships of Anemone species were reconstructed based on nuclear ITS and chloroplast markers. The molecular phylogeny is largely congruent with the morphology-based classification. Commonly used medicinal herbs are distributed in each subgenus and section, and chemical and biological studies of more unexplored taxa are warranted. Gene expression profiling and relevant "omics" platforms could reveal differential effects of phytometabolites. Genomics, transcriptomics, proteomics, and metabolomics should be highlighted in deciphering novel therapeutic mechanisms and utilities of Anemone phytometabolites.